Tennessee Civil War Monuments : An Illustrated Field Guide - Sedore, Timothy S. (Timothy Stephen) (Book collections on Project MUSE., 2020)
"Throughout Tennessee, Civil War monuments stand tall, peppering the landscape from Chattanooga to Memphis and pinpointing important events and figures within Tennessee's collective narrative. In Tennessee Civil War Monuments, Timothy S. Sedore reveals Tennessee's history-laden landscape through the lens of its many proud monuments. War monuments have been cropping up since the beginning of the commemoration movement in 1863, and Tennessee is now home to 400 memorials. Not only does Sedore provide commentary for every monument--its history and aesthetic panache--he also explores the relationships that Tennessee natives have with these historic landmarks. A detailed exploration of the monuments that enrich this Civil War landscape, Sedore's Tennessee Civil War Monuments is a guide to Tennessee's spirit and heritage."